The optimal monetary instrument for prudential purposes - Goodhard, C; Sunirand, P; Tsomocos, D (University of Oxford, 2008)
The purpose of this paper is to assess the choice between adopting a monetary base or an interest rate setting instrument to maintain financial stability. Our results suggest that the interest rate instrument is preferable, since during times of a panic or financial crisis the Central Bank automatically satisfies the increased demand for money. Thus, it prevents sharp losses in asset values and enhanced asset volatility